Livelihoods Transformation of Tuban Coastal Communities Becomes Breeder of Shrimp Vannamei (Litopenaeus vannamei) - Azhar Try Bintang; Edi Susilo; Mochammad Fattah (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
The research was conducted in the coastal community environment of Panyuran Village, Tuban District, East Java Province in May 2018. The purpose of this research is to analyze the transformation of livelihood become breeder shrimp vannamei of coastal communities at Panyuran Village Tuban District. Research methodology used in this study; the research is descriptive with an approach to the phenomenon, Type of data used qualitative, the data sources are primary data and secondary data with the sampling technique used purposive sampling and snowball sampling technique, data validation used source triangulation, data analysis used interactive analysis Miles and Huberman’s model. The results showed that the phenomenon of livelihood transformation becomes seeding shrimp vannamei influenced by internal factors and external factors. The driving factors and inhibiting factors affect the acceleration or obstruction of the transformation process. This shows that the existence of a shrimp venture can help people to survive and increase living standards.